Al-Majusi: the pioner in obstetrics - Mohamed Noor, Noraini; Faris, Waleed Fekry (IIUM Press, 2011)
The methodology adopted in this research is library based research. Data and information are collected from reliable previous works and reviews. This research is basically to explore the contribution of AI-Majusi to the field of obstetrics. The research explores the theory of how a baby being pushed during delivery process. The research also explores the content of AI-Majusi's famous book which is Kitab al-Maliki. The significant of this research is the revelation of AI-Majusi's work in the obstetrics specifically on women's reproductive anatomies and the process of delivery